Network marketing guide - Šedek, Jiří (Backstage Books, 2025)
For many years, there has been a proven path to building a stable business-without stress and unnecessary risk. Learn how to develop it in a modern and enjoyable way, so it becomes both your source of income and your passion. The book is filled with practical advice that will help both beginners and those already active in business. You will learn how to choose the right company, how to turn contacts on paper into your first clients and partners, and how to find the most talented people with whom you can build large and successful organisations. This guide is for everyone who takes network marketing seriously and wants to grow with a clear and reliable system.
Keywords: Ekonomie; Osobní rozvoj a kariéra